Everolimus-eluting bioresorbable scaffolds in patients with coronary artery disease: results from the German-Austrian ABSORB RegIstRy (GABI-R) - Nef, Holger M.; Wiebe, Jens; Kastner, Johannes; Mehilli, Julinda; Muenzel, Thomas; Naber, Christoph; Neumann, Till; Richardt, Gert; Schmermund, Axel; Woehrle, Jochen; Zahn, Ralf; Riemer, Thomas; et al. (EuroIntervention, 2017)
Aims: The aim of this study was to analyse the procedural results and midterm safety of everolimus-eluting bioresorbable vascular scaffolds (BVS) used for percutaneous coronary intervention in a large all-comers cohort from the German-Austrian ABSORB RegIstRy (GABI-R). Methods and results: A total of 3,231 patients were included in this prospective, observational, multicentre study (ClinicalTrials.gov NCT02066623) of consecutive patients undergoing BVS implantation between November 2013 and January 2016. Endpoints were major adverse cardiac events (MACE; a composite endpoint of death, target vessel revascularisation, and myocardial infarction), and target lesion failure (TLF; a composite endpoint of cardiac death, target vessel myocardial infarction, and target lesion revascularisation). Scaffold thrombosis was a further endpoint. Of all patients, 51.5% presented with acute coronary syndrome. Predilatation and post-dilatation were performed in 91.5% and 71.9% of patients, respectively. Procedural success was 98.9%. After six months, the incidence of MACE was 4.1% and of TLF 2.4%. The rate of target vessel MI was 1.5%, and target lesion revascularisation was performed in 1.8%. Definite/probable scaffold thrombosis was documented in 1.4% of patients. Conclusions: GABI-R, the largest registry to provide data regarding safety after BVS implantation in a real-world setting, reveals high procedural success and low six-month event rates.
EVALuna2:36015